End-to-side neurorrhaphy: Past, present, and future - Viterbo, Fausto; Amr, Adel Hussein; Stipp, Elisangela Jeronymo; Reis, Fabio José (My University, 2009)
To the present day, nerve injuries still represent a challenge to the surgeon. With all the advances in microneural surgery, additional approaches need to be studied to improve functional results. End-to-side nerve repair is the newest tool in managing certain nerve injuries, especially where the surgeon is faced with long nerve gaps, when it becomes impractical to use nerve grafts. The use of long nerve grafts is associated with intraneural fibrosis and atrophy of the end organs because of the prolonged time of regrowth of axons. The authors present a full review of the history, experimental work, and clinical applications of end-to-side neurorrhaphy, such as facial palsy, brachial plexus repair, and solitary sensory nerve repair. After reading this article, the surgeon will be familiar with this newest technique available to the microneural surgeon and the situations where the technique can be used to yield good results. She or he will also be able to expand on the existing experimental work in the pursuit of best functional outcomes. Copyright © 2009 by the American Society of Plastic Surgeons.